2021
DOI: 10.1097/md.0000000000024172
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers of peripheral blood mononuclear cell in hepatocellular carcinoma using bioinformatic analysis

Abstract: Background: Hepatocellular carcinoma (HCC) is the cause of an overwhelming number of cancer-related deaths across the world. Developing precise and noninvasive biomarkers is critical for diagnosing HCC. Our research was designed to explore potentially useful biomarkers of host peripheral blood mononuclear cell (PBMC) in HCC by integrating comprehensive bioinformatic analysis. Methods: Gene expression data of PBMC in both healthy individuals and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A series of steps are involved in the development of cancer cells which involve changes in growth, cell metabolism, proliferation, and adhesion (22,23). Several studies have provided information about the biomarker of liver cancer (24,25). The fact that REXO4 has been identified as a new biomarker for HCC, could aid in elucidating how alterations in cytokinesis and the immune environment stimulate the development of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A series of steps are involved in the development of cancer cells which involve changes in growth, cell metabolism, proliferation, and adhesion (22,23). Several studies have provided information about the biomarker of liver cancer (24,25). The fact that REXO4 has been identified as a new biomarker for HCC, could aid in elucidating how alterations in cytokinesis and the immune environment stimulate the development of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the interest in the fraction of peripheral blood mononuclear cells (PBMC) as a biological material for searching for biomarkers related to different diseases, e.g., obesity has grown in the last years. [16][17][18][19] Apart from their role in immunology, PBMC express a significant proportion, around 80%, of the genes encoded by the human genome and act as "sentinel" cells capable of reflecting gene expression profiles of internal tissues. [20] In fact, we have previously shown that gene expression of selected key lipid metabolism genes in human PBMC is affected by OW-OB in the same way as in crucial energy homeostatic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a decrease in the mortality rate of patients diagnosed in the early stages of the disease's progression, the overall survival (OS) for advancedstage liver cancer patients can still be improved (2). Patients are frequently identified with advanced-stage liver cancer and are unable to obtain appropriate therapy because of a lack of highly specific and specific early diagnostic biomarkers, and thus their prognosis is poor (3). It is critical to investigate new HCC markers to enhance the prognosis of HCC patients, as well as to better understand the molecular pathways driving carcinogenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%